THE EFFICACY AND SAFETY OF INFLUENZA VACCINATION IN OLDER PEOPLE: AN UMBRELLA REVIEW OF EVIDENCE FROM META-ANALYSES OF BOTH OBSERVATIONAL AND RANDOMIZED CONTROLLED STUDIES - Demurtas, Jacopo; Celotto, Stefano; Beaudart, Charlotte; Sanchez-Rodriguez, Dolores; Balci, Cafer; Soysal, Pınar; Solmi, Marco; Celotto, Daniele; Righi, Elena; Smith, Lee; Lopalco, Pier Luigi; Noventa, Vania; et al. (Ageing Research Reviews, 2020)
Vaccination is the main public health intervention to prevent influenza. We aimed to evaluate the efficacy and safety of influenza vaccination systematic reviews and meta-analyses of observational studies and randomized controlled trials (RCTs). Peer-reviewed systematic reviews with meta-analyses of prospective studies that investigated the association of influenza vaccination with any health-related outcome, as well as RCTs that investigated the efficacy and safety of influenza vaccination, were included. Among 1,240 references, 6 meta-analyses were included. In cohort studies of community-dwelling older people influenza vaccination was associated with a lower risk of hospitalization for heart disease and for flu/pneumonia (strength of evidence: convincing). Evidence in lowering the risk of mortality in community-dwelling older people, of all deaths/severe respiratory diseases in high risk community-dwelling older people and of hospitalization for flu/pneumonia in case-control studies, was highly suggestive. In RCTs, influenza vaccination, compared to placebo/no intervention, was associated to higher risk of local tenderness/sore arm and to a reduced risk of influenza like-illness. Both these associations showed moderate evidence using the GRADE (Grading of Recommendations Assessment, Development and Evaluation). In conclusion, influenza vaccination in older people seems safe and effective. Further, the evidence on safety and efficacy of vaccines in this population might benefit by an extension of the follow-up period both in RCTs and in longitudinal studies, beyond the usual 6-month period, in order to be able to evaluate the impact of vaccination on long term outcomes.
CRIS-Team Scopus Importer:2020-06-30
Keywords: flu; influenza; older people; umbrella review; vaccination